2020
DOI: 10.1002/advs.202003370
|View full text |Cite
|
Sign up to set email alerts
|

LiDFOB Initiated In Situ Polymerization of Novel Eutectic Solution Enables Room‐Temperature Solid Lithium Metal Batteries

Abstract: It is demonstrated that a novel eutectic solution including 1,3,5-trioxane (TXE) and succinonitrile (SN) can be converted into solid-state polymer electrolyte (SPE) via in situ polymerization triggered by lithium difluoro(oxalato)borate (LiDFOB). It is worth noting that all the precursors (LiDFOB, TXE, and SN) of this novel SPE are totally solid and nonvolatile at room temperature, where, LiDFOB works as a lithium salt and an initiator simultaneously to avoid the introduction of impurity. It is noted that such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 29 publications
1
78
0
Order By: Relevance
“…in 2020, Cui's group demonstrated a new kind of SN-based solid polymer electrolyte via an in situ polymerization of novel eutectic solvent including 1,3,5trioxane (TXE) and SN initiated by lithium difluoro(oxalato) borate (LiDFOB). [47] MD simulations and other characterization verified that there exists a uniform supermolecular structure in this solid-state polymer electrolyte (SPE) (Figure 11), which can significantly suppress the motion of SN and thus prevent the reaction between SN and Li metal. Meanwhile, this SPE is favorable to form robust polymer-based protective layer on LiCoO 2 and Li, simultaneously.…”
Section: Plastic Crystal Electrolytesmentioning
confidence: 80%
See 2 more Smart Citations
“…in 2020, Cui's group demonstrated a new kind of SN-based solid polymer electrolyte via an in situ polymerization of novel eutectic solvent including 1,3,5trioxane (TXE) and SN initiated by lithium difluoro(oxalato) borate (LiDFOB). [47] MD simulations and other characterization verified that there exists a uniform supermolecular structure in this solid-state polymer electrolyte (SPE) (Figure 11), which can significantly suppress the motion of SN and thus prevent the reaction between SN and Li metal. Meanwhile, this SPE is favorable to form robust polymer-based protective layer on LiCoO 2 and Li, simultaneously.…”
Section: Plastic Crystal Electrolytesmentioning
confidence: 80%
“…In addition, the interfacial Reproduced with permission. [47] Copyright 2020, John Wiley and Sons. compatibility of SN with other negative electrode materials (graphite, silicon) remains a challenge.…”
Section: Plastic Crystal Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several eutectic electrolytes have been designed for Li metal anode to prevent Li dendrite growth. [66,67] For example, Cui et al reported succinonitrile (SN)-based dual-anion DES as a highsafety electrolyte for Li metal batteries. [67] The as-fabricated SNbased DES exhibited a high ionic conductivity of 2.86 mS cm −1 with a large Li transfer number of 0.44 at 25 °C, and good interfacial compatibility toward the Li metal.…”
Section: Li-ion and Li-metal Batteriesmentioning
confidence: 99%
“…Several eutectic electrolytes have been designed for Li metal anode to prevent Li dendrite growth. [ 66,67 ] For example, Cui et al. reported succinonitrile (SN)‐based dual‐anion DES as a high‐safety electrolyte for Li metal batteries.…”
Section: Dess For Energy Storage Applicationsmentioning
confidence: 99%